Assessment of Farmers\' Attitudes towards Water Scarcity Challenge and Its Adaptation Strategies in Villages of Bahar County (Hamadan Province, Iran) - Hasan Yavarian; Hamid Jalalian; Asghar Tahmasebi (تحقیقات کاربردی علوم جغرافیایی)
Water Resource plays a pivotal role in sustainable development of every area, especially in rural areas. The challenge of dehydration is one of the greatest challenges in 21st century because it can be the source of many of the world's social and ecological changes. The agricultural sector as the most important economic sector in the rural areas is directly affected by the shortage of water resources. Identifying the attitudes and solutions of indigenous farmers in facing to water deficiency plays a key role in appropriate strategies and improving the capacity of local communities to adapt to it. The purpose of this study was to investigate the attitude of farmers in the villages of Bahar County in Hamadan province toward the challenge of dehydration and identify appropriate strategies and strategies for mitigation and adaptation in the region. This research is a descriptive-analytical study. The statistical population of the study is 68 villages in Bahar County with 18376 households. According to Cochran formula, there was needed to complete the questionnaire by 375 farmers as the number of the samples. The main data were collected through a field survey using a questionnaire. The sampling method was random and the number of samples in each village was determined by proportionate stratified sampling based on the number of farmers and the questionnaires were completed randomly. Data analysis was performed using confirmatory factor analysis in Lizrel software. The attitude of the villagers towards the aridity challenge was respectively cognitive attitude with (0.883), behavioral attitude with (0.867) and emotional attitude with (0.517) of factor analysis. Therefore, it can be concluded that the villagers' attitude to the challenge of dehydration is a cognitive-behavioral. Based on this, 12 strategies consistent with the status of the region have been proposed for optimal resource management and crop water productivity.